2010
DOI: 10.1149/1.3367920
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Effects of Organic Additives on Zinc Electrowinning from Industrial Electrolyte

Abstract: The influence of Saponin, Licorice, Tennafroth 250, and Dowfroth 250 at different concentration levels (0, 5, 10, and 15 ppm) were investigated during zinc electrowinning from industrially supplied spent electrolyte. Acid mist suppression efficiency, polarization behavior, current efficiency and energy consumption were investigated for a current density of 500 A.m -2 . Surface tension measurements were used to find a correlation between the concentration of the different additives and the acid mist suppression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…As shown in figure 8(a), the addition of 5 mg l −1 FS-101 acid mist inhibitor made the grain structure of the deposited zinc plate smaller and more closely aligned, this is similar to previous studies [34] where the addition of perfluorocarboxylic acid to an acidic zinc sulfate electrolyte resulted in smaller and more compactly arranged grain structure and better surface morphology of the deposited zinc sheets. However this is in contrast to the previous Dhak [23] study where the grain size of the microstructure of the zinc plate was larger and less densely arranged when 5 ppm SE/Saponin acid mist inhibitor was added to the electrolyte. Furthermore, no fragments and aggregation phenomenon is observed on the zinc surface, obtained in ZnSO 4 electrolyte with 5 mg l −1 FS-101 (figure 8(a)).…”
Section: Influence Of the Acid Mist Inhibitor Concentration On The De...contrasting
confidence: 93%
See 1 more Smart Citation
“…As shown in figure 8(a), the addition of 5 mg l −1 FS-101 acid mist inhibitor made the grain structure of the deposited zinc plate smaller and more closely aligned, this is similar to previous studies [34] where the addition of perfluorocarboxylic acid to an acidic zinc sulfate electrolyte resulted in smaller and more compactly arranged grain structure and better surface morphology of the deposited zinc sheets. However this is in contrast to the previous Dhak [23] study where the grain size of the microstructure of the zinc plate was larger and less densely arranged when 5 ppm SE/Saponin acid mist inhibitor was added to the electrolyte. Furthermore, no fragments and aggregation phenomenon is observed on the zinc surface, obtained in ZnSO 4 electrolyte with 5 mg l −1 FS-101 (figure 8(a)).…”
Section: Influence Of the Acid Mist Inhibitor Concentration On The De...contrasting
confidence: 93%
“…More precisely, Cheng [22] demonstrated that two saponinrich products (Mistop ® and QLZinc ® ) with a commercial licorice product can also play an active role in suppressing the generation of acid mist during the zinc electroposition process while reducing the current efficiency. Dhak [23] studied the influence of saponin, licorice, Dowfroth 250, and Tennafroth 250 on the zinc electrowinning process in industrial waste electrolytes. He deduced that all these surfactants can reduce acid mist.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of 100 mg/L zinc, with increasing adsorbate from 0-5%, the recovery efficiency of zinc decreased from 100% to 0% and the energy consumption increased from 0.0017-0.003 kwh/kg zinc. Considering the energy consumption and zinc deposit mass, 0.1% of the adsorbate is recommended for zinc electrowinning.The presence of organophosphorus-based extractants decreases metal impurities, including the concentration of Zn [17]. Ivanov's research group focused on Zn impurities through the addition of inhibitors during electrowinning [18,19].…”
mentioning
confidence: 99%
“…The presence of organophosphorus-based extractants decreases metal impurities, including the concentration of Zn [17]. Ivanov's research group focused on Zn impurities through the addition of inhibitors during electrowinning [18,19].…”
mentioning
confidence: 99%
“…[16][17][18][19] 103) and (112) planes during zinc electrowinning in sulphate system. 20,21 Alvarez and Salinas reported that addition of gelatin caused variation of instantaneous nucleation in sulphate electrolyte without additives. 22 Additionally, nucleation mechanism was also controlled by overpotential, magnetic eld, concentration of electroactive sites and temperature in acidic electrolyte.…”
Section: Introductionmentioning
confidence: 99%